Optimalisasi Smart City sebagai Media Komunikasi Pembangunan di Indonesia - Maharani Imran; Iwan Armawan (Institut Pertanian Bogor, 2019)
Cyber city is one of the modern city concepts based on Information and Communication Technology (ICT) which has been widely applied in big cities around the world. This is a result of the increasing need for people who want to access information and communicate easily and quickly. As part of the modern world community, Indonesia is time to apply the concept of cyber city to meet the needs of its citizens in accessing the internet more broadly and is no longer limited to certain groups. Indonesian citizens are now in the information age where everyone has the same opportunity to communicate widely both nationally and internationally. The implementation of cyber city can also help the community in utilizing the sophistication of information technology to support development. This study discusses the optimization of cyber city as a communication media for development in Indonesia. This study uses a qualitative approach. The data collection technique of the researcher uses the literature study method. Cyber city as a development communication media has an important role in supporting development in Indonesia, it needs to be improved development communication technology innovations that are easy to use and useful for the community and increase protection for people's personal data.